1994
DOI: 10.1038/bjc.1994.332
|View full text |Cite
|
Sign up to set email alerts
|

CA 242, a new tumour marker for pancreatic cancer: a comparison with CA 19-9, CA 50 and CEA

Abstract: The serum expression of a novel tumour marker, CA 242, defined by monoclonal antibody C 242, was studied in 179 patients with pancreatic cancer. The results were compared with CA 19-9, CA 50 and CEA. CA 242 is a carbohydrate closely related, but not identical, to CA 19-9 and CA 50. The overall sensitivity of the CA 242 assay was 74%: 55% in stage I, 83% in stage II-III and 78% in stage IV disease. The specificity calculated from 112 patients with benign diseases was 91%. CA 19-9 had a higher sensitivity of 83%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 23 publications
5
30
0
3
Order By: Relevance
“…A total of nine articles describe the diagnostic value of CA 242 for pancreatic cancer during the past 20 years. Its diagnostic performance is generally thought to be inferior to that of CA 19-9 and CA 50, but Wu et al (2006) showed an almost similar performance on 48 carcinomas and 93 matched controls with 74% sensitivity and 91% specificity (Haglund et al 1994). Jiang et al (2004a) observed even superior values with 82% sensitivity and 93% specificity in a larger study group of 96 carcinomas and 200 controls.…”
Section: Ca 242mentioning
confidence: 68%
“…A total of nine articles describe the diagnostic value of CA 242 for pancreatic cancer during the past 20 years. Its diagnostic performance is generally thought to be inferior to that of CA 19-9 and CA 50, but Wu et al (2006) showed an almost similar performance on 48 carcinomas and 93 matched controls with 74% sensitivity and 91% specificity (Haglund et al 1994). Jiang et al (2004a) observed even superior values with 82% sensitivity and 93% specificity in a larger study group of 96 carcinomas and 200 controls.…”
Section: Ca 242mentioning
confidence: 68%
“…The results achieved in the present work are in accordance with those of other authors [10], who reported a similar sensitivity of CA195 relative to the stage of the disease. In contrast, several studies have described the greatest sensitivity for CA19-9 or CA242 for identifying unresectable or large pancreatic carcinomas [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Other tumor-associated antigens such as Dupan-2, TPA, and CA 50 generally have a lower accuracy than CA 19-9 [14], However, a recent study of CA 50 [15] reported increased CA 50 serum levels in 96% of pan creatic cancer cases and in 36% of chronic pancreatitis cases. CA 50 levels combined with signs and symptoms of the patients reached a sensitivity of 91 % and a specificity of 9 5%.…”
Section: Additional Tumor Markers In Pancreatic Cancermentioning
confidence: 99%